Genotype by environment interactions in soybean for agronomic traits and nodule formation - Magagane, Tshepo Gordene (My University, 2011)
The nature and magnitude of the genotype by environment interactions is important to identify superior and stable genotypes under the target environments. This will assist to maximize specific adaptation and to speed up the transfer of new cultivars to growers. The objective of this study was to determine the stability of selected soybean genotypes with regards to the agronomic traits, high yield and nodule formation. Field experiments were conducted under dryland conditions during the 2007/2008 and 2008/2009 growing seasons at the University of Limpopo’s experimental farm (Syferkuil) and at a farmer’s field at Gabaza community, Mopani District near Tzaneen. Ten selected soybean cultivars were evaluated under a randomised complete block design with three replications. Stability was assessed via joint regression and superiority analyses. Significant differences were found for genotypes, environments and genotype by environment interactions. Stability analysis after Eberhart and Russell’s model suggested that the genotypes showed marked differences to environmental changes. The cultivar superiority measure for seed yield indicated that variety Clark was the most stable genotype with an average yield of 5235 kg/ha, followed by L81-4858 and Barc-2 that provided average yield of 4839 kg/ha and 4582 kg/ha, respectively. In terms of number of nodules Magoye was observed to be stable with average of five nodules per plant. Cultivar Barc-2 was found stable for number of active nodules with an average of 3.17 active nodules per plant. Most of the genotypes performed better at Syferkuil than at Gabaza. In general Barc-2 was found stable for yield and other agronomic traits considered in this study. This variety could be suitable for large scale production in these or other similar environments in Limpopo Province.
Thesis (M.Sc. Agriculture (Crop Science)) -- University of Limpopo, 2011
Keywords: Soybean; Agronomic traits; Soybean -- Breeding; Genotype-environment interaction; Soybean -- Effect of temperature on; Soybean -- Genetics